MANAJEMEN KEUANGAN DI MADRASAH IBTIDA’IYAH TARBIYATUS SYARIFAH SIDOARJO - novita, Siti Masitho Novita; M. Athoiful Fanan (AL-MAFAZI: JURNAL MANAJEMEN PENDIDIKAN ISLAM, 2024)
Educational financial management is a process of activities that have been prepared and will be carried out and attempted periodically against school operational costs so that educational activities are more effective and efficient in achieving educational goals. Financial management at the Madrasah Ibtida'iyah Tarbiyatus Syarifah school is able to apply the concept of transparency so it is interesting to study. This study aims to find out how the Madrasah Ibtida'iyah Tarbiyatus Syarifah school management manages school finances. The research approach used in this research is qualitative research or commonly called descriptive research where the data collection is taken from interviews, observation and documentation. The data analysis technique uses Mod Miles and Huberman which begins with data collection, data presentation and finally draws conclusions. The results of this study indicate that: 1). Financial management that is implemented at MI Tarbiyatus Syarifah starting from Budgeting, Bookkeeping and Examination 2) there are supporting and inhibiting factors for MI Tarbiyatus Syarifah's financial management, the existence of these supporting factors is characterized by sufficient technology, adequate supervision and auditing independence and so on.